Banks' interest rate risk and search for yield: A theoretical rationale and some empirical evidence - Christoph Memmel; Atılım Seymen; Max Teichert (Deutsche Bundesbank, 2016)
We investigate German banks' exposure to interest rate risk. In finance, higher demand for a risky asset is typically associated with higher expected return. However, employing a utility function which implies both risk-averse and risk-seeking behavior depending on the level of profits, we show that this relationship may get weaker and even change its sign at low profit levels. For the period 2005-2014, we find not only the common positive relationship of higher expected returns and rising interest rate exposure but also that this relationship does become weaker with falling operative income, its sign eventually changing.
Keywords: G11; G21; 330; banks' risk taking; exposure to interest rate risk; low interest rate environment